The risk factors for postpartum posttraumatic stress disorder and depression - BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (WILEY, 2020)
Purpose In this study, we examined the association between specific birth-related variables and postpartum posttraumatic stress disorder (PTSD) and depressive symptoms. Design and Methods In this descriptive study, data were collected using a personal information form, the City Birth Trauma Scale, and the Edinburgh Postpartum Depression Scale. Findings The findings revealed that 8.5% of participants met all the diagnostic criteria for PTSD. The risk of developing depression was 9.7 times higher among women who met all the criteria for PTSD than among those who did not meet all the criteria. Practice Implications During the postpartum period, at-risk mothers should be followed and screened for PTSD and depressive symptoms.
Keywords: childbirth; postpartum; postpartum depression; postpartum posttraumatic stress disorder; SYMPTOMS FOLLOWING CHILDBIRTH; BIRTH; PREGNANCY; MODEL